76.7k views
5 votes
Are all expressions shown below equivalent? 8.1 + 12 4(2x + 3) 6x + 12 + 2x 8(x + 1) + 4

User GilbertOOl
by
4.8k points

1 Answer

5 votes

OK

First simplify all expression

1. 8x + 12 = 8x + 12

2. 4(2x + 3 ) = 8x + 12

3. 6x + 12 + 2x = 6x + 2x + 12 = 8x + 12

4. 8(x + 1) + 4 = 8x + 8 + 4 = 8x + 12

we can see that all expressions are equal, hence all are equivalent.

User FrodoB
by
6.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.